Structural components of the normal thoracic and lumbar vertebrae in rats - M. V. Pankiv; Ye. V. Paltov; Z. Z. Masna (Kazimierz Wielki University, 2021)
The relevance of this topic is determined by the fact that laboratory animals are widely used in experimental morphology. The most widely used ones are rats [1 - 7]. There are a number of studies in which the authors cover in detail the normal morphological state of various organs of rats and its changes under experimentally simulated pathological conditions [8 - 12]. The available studies on the rats' musculoskeletal system and spine highlight this topic insufficiently. Aim. We aimed to study the structure of the normal thoracic and lumbar vertebrae in the rats. Materials and methods of research. The objects of our study were 15 sexually mature outbred male rats, weight 80 g, age 4,5 months. All animals were kept in a vivarium. Keeping, care, labeling, and all other manipulations were carried out in accordance with with 'the European Convention for the Protection of Vertebrate Animals Used for Experimental and Other Scientific Purposes' [Strasbourg, 1985], 'Ethical principles of animal experiments', approved by the First National Congress on Bioethics [Kyiv, 2001], Law of Ukraine № 3447 - IV 'On protection of animals from cruel treatment'. The study was approved by the Commission on Bioethics of Danylo Halytsky Lviv National Medical University which declared that the study met the ethical requirements according to the order of the Ministry of Health of Ukraine № 231 of November 1, 2000 (protocol № 10 of December 26, 2011), (protocol №2 of February 20, 2012 year). Before sampling, the animals were sedated with dibutyl ether. Skeletalized rat bones were used as material for the macroanatomical study of the structural components of the thoracic and lumbar vertebrae. The spines were dissected after euthanasia, and then the vertebrae of the thoracic and lumbar spine were boiled for four hours, followed by careful separation of the remained soft tissues. The obtained bones were treated with a solution of hydrogen peroxide with the following photography in different projections in order to identify all anatomical structures involved in the formation of thoracic and lumbar vertebrae. Photography was made using a digital camera Nikon D 3100. Results. The study of 15 spinal column preparations of white, outbred male rats weighing 80 g, aged 4.5 months made by the use of a set of morphological methods revealed a lot of aspects of the normal structural components of the vertebrae of the lower thoracic and lumbar spine of rats. The spinal column of the rat consists of a set of vertebrae that form its divisions. There are 57 vertebrae in the rat spine. The cervical division is represented by 7 vertebrae, thoracic - 13, lumbar - 6, sacral - 4 and caudal - 27 vertebrae. Conclusions: As a result of our study, we identified the morphology of normal vertebrae of the thoracic and lumbar spine in rats. We studied a set of morphological components of the thoracic and lumbar vertebrae of the normal spinal column in rats.